A novel composite for thermal energy storage from alumina hollow sphere/paraffin and alkali-activated slag. Issue 11 (1st June 2021) - Sang, Guochen; Du, Xiaoyun; Zhang, Yangkai; Zhao, Caiyun; Cui, Xiaoling; Cui, Hongzhi; Zhang, Lei; Zhu, Yiyun; Guo, Teng
Abstract: This study proposes a novel thermal energy storage composite (TESC) with an alumina ceramic-based form-stable phase change material (FSPCM) as the phase-change aggregate and alkali-activated slag as the matrix material. FSPCM was prepared with alumina hollow sphere as the supporting material and paraffin as the phase change material (PCM). A series of tests were conducted to investigate the thermo-mechanical properties of the TESC. The results show that the phase transition peak temperature of FSPCM is 23.6 °C, the latent heat value is 69.8 J/g, and the paraffin adsorption mass fraction with respect to the alumina hollow sphere can be as high as 82.33%. As the mass fraction of FSPCM increases from 0% to 80%, the latent heat value increases from 0 J/g to 19.18 J/g, while the compressive strength can still be maintained above 24.04 MPa. The effective thermal penetration depth and the thermal energy storage performance of the TESC were mathematically analysed and experimentally tested. Meanwhile, the influence of FSPCM dosage on the mechanical strength of the TESC and the microstructure characteristics of the interface transition zone between FSPCM and the matrix were investigated. A mathematical model with a maximum relative error of 12.08% was established for predicting the 28-day compressive strength of TESC.